2015
DOI: 10.1063/1.4929507
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependent damping in nanomechanical resonators from thin MoS2 crystals

Abstract: We investigate the effect of mechanical strain on the dynamics of thin MoS 2 nanodrum resonators.Using a piezoelectric crystal, compressive and tensile biaxial strain is induced in initially flat and buckled devices. In the flat device, we observe a remarkable strain-dependence of the resonance line width, while the change in the resonance frequency is relatively small. In the buckled device, the strain-dependence of the damping is less pronounced, and a clear hysteresis is observed. The experiment suggests th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 36 publications
(49 reference statements)
4
32
0
Order By: Relevance
“…Referring to Figure 4, to detect the resonance of the MoS 2 drum, we used an optical fiber F-P interferometric method rather than the free-space optical actuation one described previously [7,9,16,17,18,19]. Resonator motion was actuated using a 1550.12-nm amplitude-modulated distributed feedback (DFB) laser S (10 dBm output power) that excited motion through photothermal expansion and contraction of the MoS 2 diaphragm via an electro optic modulator (EOM) with power amplification.…”
Section: Experiments and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Referring to Figure 4, to detect the resonance of the MoS 2 drum, we used an optical fiber F-P interferometric method rather than the free-space optical actuation one described previously [7,9,16,17,18,19]. Resonator motion was actuated using a 1550.12-nm amplitude-modulated distributed feedback (DFB) laser S (10 dBm output power) that excited motion through photothermal expansion and contraction of the MoS 2 diaphragm via an electro optic modulator (EOM) with power amplification.…”
Section: Experiments and Analysismentioning
confidence: 99%
“…Furthermore, ultralow areal mass density of 3.3 fg/μm 2 , high elastic modulus (~0.3 TPa), and an exceptional strain limit of 10%~12% [14] make it an attractive alternative to graphene, which typically has higher energy dissipation [15], especially in air damping due to a smaller thickness per unit layer and lower mass density [7]. For these reasons, much effort has been made to characterize the resonance behaviors of NEMS devices made of single-layer, few-layer, or multilayer MoS 2 films in a vacuum chamber using electrical or optical excitation at room temperature [16,17,18,19]. Lee et al reported on the demonstration of MoS 2 nanodevices, where MoS 2 diaphragms as thin as 6 nm exhibited fundamental-mode nanomechanical resonances up to ~60 MHz in the very high frequency band, and frequency- Q factor products up to ~2 × 10 10 Hz [16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations